A novel fuzzy‐based structured framework for sustainable operation and environmental friendly production in coal‐fired power industry. Issue 4 (31st May 2021) - Panchal, Dilbagh; Chatterjee, Prasenjit; Pamucar, Dragan; Yazdani, Morteza
Abstract: This study proposes a novel structured framework for analyzing sustainable operational performance‐related issues of ash handling unit (AHU) under vague/uncertain information and its impact on ecofriendly production. The structured framework is developed using an integrated fuzzy lambda–tau and fuzzy multicriteria decision‐making methods. Reliability parameters are formulated for assessing the failure behavior of AHU using the fuzzy lambda–tau approach. Repair time parameter for the AHU system shows an increasing trend with a 0.6840% increase as the spread increases from ±15% to ±25% and 0.5981% when spread increases from ±25% to ±60%. Furthermore, the availability of the system decreases by 0.0335% with increase in spread from ±15% to ±25% and further decreases to 0.0315% with spread increases from ±25% to ±60%. Under risk analysis, possible failure causes with their fuzzy rating are listed under the failure mode and effect analysis (FMEA) approach. Evaluation based on distance from average solution (EDAS) and combinative distance‐based assessment (CODAS) methods are further applied within the FMEA approach for identifying the most critical failure causes. Improper design (BT2 ), excessive gas volume (FH3 ), chocking/blockage (WA1 ), and scanty lubrication/greasing (SP1 ) associated with bottom ash handling,  the fly ash handling system, wetting unit and ash disposal pipeline, and slurry pump with EDAS outputs (0.1464,  0.1090,  0.0918,  0.000) and CODAS outputs (3.3962,  3.5208,  2.6562,  2.0877) are found responsible for sudden failure of the considered unit. Sensitivity analysis has been done for evaluating the robustness of the proposed framework.